MicroRNA-142-3p Inhibits Tumorigenesis of Colorectal Cancer via Suppressing the Activation of Wnt Signaling by Directly Targeting to β-Catenin - Liu, Peng; Cao, Fuao; Sui, Jinke; Hong, Yonggang; Liu, Qizhi; Gao, XianHua; Gong, Haifeng; Hao, Liqiang; Lou, Zheng; Zhang, Wei (Frontiers in Oncology, 2021)
Background Altered expression profile of microRNAs (miRNAs) was reported to be associated with colorectal cancer (CRC). The aims of this study are to identify the changed miRNAs in the plasma of CRC patients and explore the underlying mechanism of these miRNAs during tumorigenesis. Methods Plasma miRNA expression profiles were compared between healthy people and CRC patients. MiRNA expression was measured using quantitative real-time PCR. Colony formation and MTT assays were used to test cell proliferation. Luciferase assay, immunohistochemistry and Western blotting were employed to explore the molecular mechanism. Results MiR-142-3p level was found as the most significantly repressed miRNA in CRC patients. Overexpression of miR-142-3p dramatically repressed colony formation and cell proliferation of both HT29 and HCT116 cells while inhibition of miR-142-3p promoted those of the cells. Interestingly, overexpression of miR-142-3p reduced the level and nuclear accumulation of β-catenin. We further observed that miR-142-3p remarkably inhibited the transcriptional activity of β-catenin gene (CTNNB1). However, mutations in the predicted binding sites blocked this inhibition, suggesting that miR-142-3p may directly bind to the mRNA of β-catenin. Conclusion In conclusion, we identified miR-142-3p exerts its function as a tumor suppressor through blocking the activation of Wnt signaling by directly targeting to CTNNB1.